THE SIGNIFICANCE OF KEEPING THE CADASTRE OF LANDS INTENDED FOR THE PURPOSES OF RECREATION AND SANITATION OF NATURAL AREAS (American Journal of Research in Humanities and Social Sciences, 2024)
In the scientific article, issues such as improvement of cadastral documentation of lands intended for the purpose of rehabilitation and recreation through modern methods, development of scientific methodical bases and substantiation of directions for improvement of cartographic tools are presented.